2016
DOI: 10.1590/abd1806-4841.20164456
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical psoriasis after the use of anti-TNF in a patient with rheumatoid arthritis

Abstract: The use of tumor necrosis factor antagonists (anti-TNF) has become a usual practice to treat various inflammatory diseases. Although indicated for the treatment of psoriasis, anti-TNF may paradoxically trigger a psoriasiform condition. We present a case of a female patient who, during the use of infliximab for rheumatoid arthritis, developed psoriasis. In an attempt to switch anti-TNF class, we observed a cumulative worsening of the lesions requiring suspension of the immunobiological agent and the introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Altta yatan hastalıktan ve kullanılan ajandan bağımsızdır. [1,2] PPs olgularımızın ikisinde yeni başlangıçlı psöriatik lezyonlar, son olgumuzda ise mevcut lezyonlarda kötüleşme olarak ortaya çıkmıştı. Collamer'in [4] TNF'nin Th17 ve Treg hücreler üzerindeki immün regulatuvar etkisinin anti-TNF tedaviyle ortadan kalkması ve proinflamatuvar sitokin interferon-alfa ile TNF arasındaki dengenin bozulması PPs patogenezinden sorumlu tutulan 2 mekanizmadır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Altta yatan hastalıktan ve kullanılan ajandan bağımsızdır. [1,2] PPs olgularımızın ikisinde yeni başlangıçlı psöriatik lezyonlar, son olgumuzda ise mevcut lezyonlarda kötüleşme olarak ortaya çıkmıştı. Collamer'in [4] TNF'nin Th17 ve Treg hücreler üzerindeki immün regulatuvar etkisinin anti-TNF tedaviyle ortadan kalkması ve proinflamatuvar sitokin interferon-alfa ile TNF arasındaki dengenin bozulması PPs patogenezinden sorumlu tutulan 2 mekanizmadır.…”
Section: Discussionunclassified
“…Anti-TNF tedavi alan hastaların %2-5'inde görülür. [1] Anti TNF'lerin ortak bir yan etkisidir. [2] Altta yatan hastalıktan bağımsızdır.…”
unclassified
“…The use of medications such as oral contraceptives, retinoids, epidermal growth factor inhibitors, and indinavir (a protease inhibitor) are associated with the appearance of lobular capillary hemangioma 3, 4, 5, 6. The use of tumor necrosis factor antagonists (anti-TNFs) has become a common practice in the treatment of various inflammatory diseases 7 . There is a case report in the literature suggesting an association of pyogenic granuloma with the use of etanercept.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 222 patients with IBD treated with anti-TNF-α, with paradoxical reaction showed that most were adult women, with CD treated with infliximab. 1,3,9 Paradoxical psoriasiform reactions can be divided clinically into de novo psoriasis and exacerbation of preexisting psoriasis. The first, which is more common and more extensively described in the literature, occurs in patients without a history of psoriasis who are receiving TNF-α therapy for another inflammatory disorder.…”
Section: Discussionmentioning
confidence: 99%